Coronavirus Disease 2019 in Chronic Kidney Disease: A Case Report - Jalmas, Dela Hangri; Fauzar, Fauzar; Kurniati, Roza; Viotra, Deka; Harun, Harnavi; Yoga, Vesri; Kam, Alexander (Jurnal Kesehatan Andalas, 2021)
The COVID-19 pandemic has caused substantial morbidity and mortality worldwide. Older patients, male gender and those with preexisting comorbidities such as chronic kidney disease are reported to be more likely infected with SARS CoV-2 and are at higher risk of severe illness or death. It has been reported a 24 years old male was admitted to the hospital with shortness of breath, coughing, fever and paleness. The history of contact with confirmed COVID-19 cases was unclear. The patient works as a security officer. A history of hypertension is present. Laboratory results showed hemoglobin 7 g/dl, ureum 261 mg/dl, and creatinine 22,9 mg/dl. On the second day of admission, the patient experience increased shortness of breath, decreased consciousness and epistaxis. From the result of the nasopharyngeal swab, the patient tested positive for COVID-19 and was given Oseltamivir 75mg. The patient is prepared for hemodialysis, which was performed in the isolation room. After hemodialysis, the patient's condition improved with decreased shortness of breath and increased of consciousness. The patient comes out from the isolation room and discharges home in good condition. Antiviral therapy in CKD patients with Covid-19 infection requires dose adjustment. Immediate hemodialysis is required in patients with CKD and coexisting COVID-19 infection to improve the patient's condition. Prompt management for patients with CKD and COVID-19 will reduce the risk of mortality.Keywords: Â COVID-19, chronic kidney disease, hemodialysis